Indexes of physical capacity and repeated sprint ability of young soccer players - Angius, L.; Olla, S.; Piras, F.; Mura, R.; Ibba, G.; Todde, F.; Cominu, M.; Pinna, M.; Tocco, F.; Concu, A.; Crisafulli, A. (Sport Sciences for Health, 2013)
Repeated sprint ability (RSA) is thought to be an important skill for team sports. However, there is no study that correlates aerobic capacity (AC) and lactic anaerobic capacity (LAC) with RSA in young elite soccer players. Fourteen young players from a professional soccer team underwent two laboratory tests: an incremental exercise test (IET) and an all-out test (AOT) to asses AC and LAC, respectively. Athletes also performed a field RSA test. During both the IET and the AOT tests heart rate, oxygen uptake, carbon dioxide production, and pulmonary ventilation were obtained by a portable gas analyzer. Velocity and fatigue indices were measured during the RSA test. Blood lactate was also measured after the AOT (BLaAOT) and the RSA (BLaRSA) test. No correlation was found between AC and LAC indices and measures of the RSA test, even though the AOT test appeared to fully recruit LAC capacity, as no difference between BLaAOT and BLaRSA was detected. It was concluded that no correlation exists between AC and LAC capacities obtained in the laboratory setting and velocity and fatigue measures from RSA testing. This finding should be taken into account when testing young soccer players.